The Principal's Leadership Model in Integrating Islamic Values ​​into School Culture at Imelda Vocational School, Medan - Daud, Muhammad; Panggabean, Hadi Saputra (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study investigates how transformative school leadership integrates character values into the school culture of Imelda Health Vocational School Medan through ethno-social pedagogical practices. The main objective is to analyze the principal’s leadership model and its contribution to strengthening character formation grounded in the school’s socio-cultural context. The study is based on the premise that school leadership extends beyond administrative duties toward shaping a value-oriented educational ecosystem. Methodology: A qualitative design was employed using in-depth interviews, participatory observation, and document analysis. Data were processed through Miles and Huberman’s interactive analysis model consisting of data reduction, data display, and conclusion drawing. Main Findings: The findings reveal two interconnected dimensions of leadership practice. First, the managerial dimension includes policy development, standard operating procedures, human resource capacity-building, the teaching factory curriculum, and evaluation systems that embed character-oriented principles. Second, the cultural and ethical dimension is demonstrated through the leader’s moral exemplarity, consistent ethical conduct, and humanistic disciplinary narratives. Together, these practices cultivate a shared cultural habitus that reinforces character development and strengthens the school’s socio-pedagogical environment. Novelty/Originality of this study: This study proposes an integrative framework of transformative leadership that blends managerial system design with socio-cultural character formation. The model contributes to character education policy and implementation by demonstrating how socio-cultural values can shape school culture and guide value-based decision-making. It adds to contemporary scholarship by linking transformative leadership, character formation, and ethno-social pedagogy within vocational education.